Cultural studies on mycelia of Pleurotus ostreatus (Oyster Mushroom) - Nidhi R; Dr. Deepika Sud (Mushroom Research, 2023)
A series of experiments were conducted to find the influence of various culture media, temperature, pH level and light intensity on mycelial growth of P. ostreatus on ten solid and liquid culture media. Yeast malt agar (8.50 cm) and Potato dextrose yeast broth (10.17 gm/ml) supported best growth of P. ostreatus followed by Malt extract agar (8.43 cm) and Yeast malt broth (9.92 gm/ml). Temperature range of 25oC was found optimum for both solid and liquid media with mycelial growth of 8.53 cm (YMA) and mycelial mat of weight 9.91 gm/ml (PDY) broth. The maximum mycelial diameter was recorded at pH 6.5 with mycelial growth of 8.19 cm in solid medium (YMA) and in liquid medium (PDY) broth maximum mycelial mat was recorded at pH 6.0 with mycelial weight of 9.98 gm/ml. Light intensity of 200 lux supported the best mycelial growth in solid (8.26 cm) as well as liquid medium (10.11gm/ml).